Low‐dose Magnesium Sulfate Versus High Dose in the Early Management of Rapid Atrial Fibrillation: Randomized Controlled Double‐blind Study (LOMAGHI Study). (25th October 2018) - Bouida, Wahid; Beltaief, Kaouthar; Msolli, Mohamed Amine; Azaiez, Noussaiba; Ben Soltane, Houda; Sekma, Adel; Trabelsi, Imen; Boubaker, Hamdi; Grissa, Mohamed Habib; Methemem, Mehdi; Boukef, Riadh; Dridi, Zohra; et al.
Abstract: Objectives: We aim to determine the benefit of two different doses magnesium sulfate (MgSO4 ) compared to placebo in rate control of rapid atrial fibrillation (AF) managed in the emergency department (ED). Methods: We undertook a randomized, controlled, double‐blind clinical trial in three university hospital EDs between August 2009 and December 2014. Patients > 18 years with rapid AF (>120 beats/min) were enrolled and randomized to 9 g of intravenous MgSO4 (high‐dose group, n  = 153), 4.5 g of intravenous MgSO4 (low‐dose group, n  = 148), or serum saline infusion (placebo group, n  = 149), given in addition to atrioventricular (AV) nodal blocking agents. The primary outcome was the reduction of baseline ventricular rate (VR) to 90 beats/min or less or reduction of VR by 20% or greater from baseline (therapeutic response). Secondary outcome included resolution time (defined as the elapsed time from start of treatment to therapeutic response), sinus rhythm conversion rate, and adverse events within the first 24 hours. Results: At 4 hours, therapeutic response rate was higher in low‐ and high‐MgSO4 groups compared to placebo group; the absolute differences were, respectively, 20.5% (risk ratio [RR] = 2.31, 95% confidence interval [CI] = 1.45–3.69) and +15.8% (RR = 1.89, 95% CI = 1.20–2.99). At 24 hours, compared to placebo group, therapeutic response difference was +14.1% (RR = 9.74, 95% CI = 2.87–17.05) with low‐dose MgSO4 and +10.3% (RR = 3.22, 95% CI = 1.45–7.17) with high‐dose MgSO4 . The lowest resolution time was observed in the low‐dose MgSO4 group (5.2 ± 2 hours) compared to 6.1 ± 1.9 hours in the high‐dose MgSO4 group and 8.4 ± 2.5 hours in the placebo group. Rhythm control rate at 24 hours was significantly higher in the low‐dose MgSO4 group (22.9%) compared to the high‐dose MgSO4 group (13.0%, p = 0.03) and the placebo group (10.7%). Adverse effects were minor and significantly more frequent with high‐dose MgSO4 . Conclusions: Intravenous MgSO4 appears to have a synergistic effect when combined with other AV nodal blockers resulting in improved rate control. Similar efficacy was observed with 4.5 and 9 g of MgSO4 but a dose of 9 g was associated with more side effects.